2023
DOI: 10.1039/d2an01804g
|View full text |Cite
|
Sign up to set email alerts
|

Classical thiazole orange and its regioisomer as fluorogenic probes for nucleolar RNA imaging in living cells

Abstract: In contrast to well-established DNA-selective dyes for live cell imaging, RNA-selective dyes have been less developed due to the challenge to make small molecules have the RNA selectivity over DNA....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 63 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Our group also reported that TO worked as a fluorogenic dye for nucleolar RNA imaging in living cells ( Φ bound = 0.16). 23 The examination with synthetic RNA and DNA revealed that TO prefers RNA over DNA, with a significant response to double-stranded RNA (rG/rC and rA/rU) and single-stranded rG. 23 In addition, TO and its derivative (TO-PRO-1) were reported as indicators in the FID assay for targeting various RNA structures including TAR RNA and the bacterial ribosomal RNA A-site, 6,7 a being apparently characterized as non-selective for TAR RNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group also reported that TO worked as a fluorogenic dye for nucleolar RNA imaging in living cells ( Φ bound = 0.16). 23 The examination with synthetic RNA and DNA revealed that TO prefers RNA over DNA, with a significant response to double-stranded RNA (rG/rC and rA/rU) and single-stranded rG. 23 In addition, TO and its derivative (TO-PRO-1) were reported as indicators in the FID assay for targeting various RNA structures including TAR RNA and the bacterial ribosomal RNA A-site, 6,7 a being apparently characterized as non-selective for TAR RNA.…”
Section: Resultsmentioning
confidence: 99%
“…23 The examination with synthetic RNA and DNA revealed that TO prefers RNA over DNA, with a significant response to double-stranded RNA (rG/rC and rA/rU) and single-stranded rG. 23 In addition, TO and its derivative (TO-PRO-1) were reported as indicators in the FID assay for targeting various RNA structures including TAR RNA and the bacterial ribosomal RNA A-site, 6,7 a being apparently characterized as non-selective for TAR RNA. Apparently, our FiLuP probe does function distinctly from the previous Tat peptide-based probes 8,11,12 as well as TO itself, having prominent binding and fluorescence properties toward TAR RNA.…”
Section: Resultsmentioning
confidence: 99%